GWPR Model on Indonesian Economic Growth: The Analysis of Spatially Varying Relationships - Santoso, Edy; Hadi Priyono, Teguh; Istiyani, Nanik; Jumiati, Aisah; Yunitasari, Duwi (Signifikan: Jurnal Ilmu Ekonomi, 2025)
Research Originality: This research is original in examining the spatial varying relationship on economic growth in Indonesia.Research Objectives: This study investigates the variability of Indonesia's economic growth model determinants.Research Methods: This study uses the Geographically Weighted Panel Regression (GWPR) approach. Panel data was analyzed with 34 provinces in Indonesia from 2016 to 2022.Empirical Results: This study found that the Revenue Sharing Fund (DBH) variable significantly influenced economic growth in 32 provinces. Meanwhile, the influence of DBH is not significant in only two provinces, namely Papua and West Papua. The variables of Labor and Gross Fixed Capital Formation did not have a significant effect on economic growth in 34 provinces.Implications: These results show that Indonesia's economic growth rate is still not optimal, so the government is expected to design development programs that integrate various factors, such as maximizing Revenue Sharing Fund management, improving the quality of labor, and maximizing capital efficiency, to encourage economic growth in all provinces.JEL Classification: C31, O47, R11, H54How to Cite:Santoso, E., Priyono, T. H., Istiyani, N., Jumiati, A., & Yunitasari, D. (2025). GWPR Model on Indonesian Economic Growth: The Analysis of Spatially Varying Relationships. Signifikan: Jurnal Ilmu Ekonomi, 14(1), 37-52. https://doi.org/10.15408/sjie.v14i1.44771.